2. Funerary Treatment of Immature Deceased in Neolithic Collective Burial Sites in France. Were Children Buried with Adults? (AmS-Skrifter, 2019)
In France, collective burial sites of the Late Neolithic period (3600-2100 BC) include a variety of structures ranging from simple pits and natural caves to hypogea and megalithic structures. The management of these graves raises questions about their representativeness and about burial practices involving non-adult individuals. This study of funerary selection based on age-at-death compares the results obtained for different sites and offers several potential interpretations concerning the integration of immature individuals in these collective tombs based on their age. The study highlights a particular selection observed in various funerary structures and a chronological difference between northern and southern France. These first results lead to a discussion of distinct cultural choices among different geographical areas.